2011
DOI: 10.1186/1756-3305-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Small risk of developing symptomatic tick-borne diseases following a tick bite in the Netherlands

Abstract: BackgroundIn The Netherlands, the incidence of Lyme borreliosis is on the rise. Besides its causative agent, Borrelia burgdorferi s.l., other potential pathogens like Rickettsia, Babesia and Ehrlichia species are present in Ixodes ricinus ticks. The risk of disease associated with these microorganisms after tick-bites remains, however, largely unclear. A prospective study was performed to investigate how many persons with tick-bites develop localized or systemic symptoms and whether these are associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 40 publications
6
57
0
Order By: Relevance
“…16%), whilst the percentage of infected larvae accounted for approx. 2% [41]. These studies indicate considerable differences in the individual forms of development of infected ticks, with a predominance of the adult form and a minor proportion of specimens infected in the larval stage.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16%), whilst the percentage of infected larvae accounted for approx. 2% [41]. These studies indicate considerable differences in the individual forms of development of infected ticks, with a predominance of the adult form and a minor proportion of specimens infected in the larval stage.…”
Section: Discussionmentioning
confidence: 90%
“…Nymphs were also prevalent in the Swiss study (64%), with significantly fewer females (33.3%) and larvae (1.6%) [40]. By contrast, the breakdown of the Dutch research was 56% of nymphs, 28% of females and 16% of the larvae [41]. Nymphs also prevailed in the Italian research (41%), with less females (34.6%) and the least larvae (8.4%) [43]which cause effects in animals and humans, commonly referred to as to tick-borne diseases (TBDs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…B. microti is a natural parasite of microtine rodents and occurs mainly in the United States. However, a case of autochthonous B. microti infection has been confirmed in a German patient with an acute myeloid leukaemia [7], and serological evidence of human B. microti infections in a number of different European countries has been reported ( Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This means that ticks attached to these sites fed for a longer time before they are detected, which would be more permissive for a potential Borrelia transmission (Crippa et al, 2002;Kahl et al, 1998). It has earlier been shown that tick-bitten people that remove ticks later than 24 hours of tick attachment, as self-estimated by the bitten persons, are more likely to develop localized and systemic symptoms (Tijsse-Klasen et al, 2011), probably due to injected tick salivary gland proteins and/or due to transmitted pathogens. We observed that participants who contracted a Borrelia infection (seroconversion) during the three-month study period detected and removed "their" Borrelia-infected ticks later (median 58 hours) than non-infected participants bitten by Borrelia-infected ticks (median 29 hours, IV).…”
Section: Which Factors May Facilitate Borrelia Transmission From Tickmentioning
confidence: 99%